2021
DOI: 10.1039/d1tc00438g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of elemental two-dimensional metals

Abstract: Two-dimensional (2D) elemental metals have attracted considerable attention owing to their fascinating physical properties and diverse potential applications. The single-atom-thick phases of metallic elements in the periodic table had been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Even when nonmagnetic elements (X = Sr, Ba, Ti, Zr, Hf, V, Ru, Os, Rh, and Ir) are included, finite magnetic moments appears due to the different profile of electron bands between up and down spins (see the Supplemental Material). This tendency is similar to the DFT calculations for 2D elemental metals 6 . The CuX tends to have smaller mag-netic moment than AgX and AuX.…”
Section: Electronic and Magnetic Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…Even when nonmagnetic elements (X = Sr, Ba, Ti, Zr, Hf, V, Ru, Os, Rh, and Ir) are included, finite magnetic moments appears due to the different profile of electron bands between up and down spins (see the Supplemental Material). This tendency is similar to the DFT calculations for 2D elemental metals 6 . The CuX tends to have smaller mag-netic moment than AgX and AuX.…”
Section: Electronic and Magnetic Propertiessupporting
confidence: 88%
“…In general, reduced dimensionality can have a possibility for enhancing the magnitude of magnetic moments 42 . It has been recently predicted that 18 elemental metals show a finite magnetic moment in the 2D structures, while there are only 5 magnetic elements in the 3D structures 6 . Also, the Cu-based compounds in the BHC structure exhibit a relatively high magnetic moment, compared to the 3D counterparts 20 .…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that a few compounds show a finite magnetic moment: For the BHC structure, CuTi (0.87); for the B2 structure, CuHg (0.47), CuIr (0.47), CuRe (2.28), CuRh (1.02), and CuZr (0.01); and for the L1 structure, CuHf (0.01), CuRh (0.72), and CuZr (0.05), where the figure in parenthesis is in units of per a cell. It has been shown that the 2D elemental metals of Ba, group 2 (Sc and Y), group 3 (Ti, Zr, and Hf), V, group 8 (Ru and Os), group 9 (Rh and Ir), and group 10 (Pd and Pt) can have a finite magnetic moment 12 . This has been attributed to a decrease in the coordination number as well as a change in the electron DOS shape.…”
Section: Methodsmentioning
confidence: 99%
“…A significant contribution have been made by Koskinen and co‐workers to explore the stability and formation of 2D metals based on the density functional theory studies [74–79] . Recently, the stability and magnetic properties of atomically thin two‐dimensional metal monolayers are explored [80,81] …”
Section: Introductionmentioning
confidence: 99%